Reconsidering Narrative Closure in the Eighteenth Century: Transfictionality in Mauvillon’s Continuation of Prévost’s Mémoires d’un honnête homme - Benjamin H. Baker (Itinéraires)
While scholars generally use the concept of transfictionality to describe narrative crossover between separate works, this limitation does not apply in the eighteenth century, when publication in multiple installments and evolving ideas about the concept of copyright made created transfictional relationships within individual works. Comparative analysis of Prévost’s Mémoires d’un honnête homme and its continuation by Éléazar de Mauvillon shows that neither the text’s plural authorship nor the material separation of its parts suffice to determine the transfictionality of this textual ensemble. Rather, Mauvillon created a transfictional work by modifying the relationship between the narrative structure of Prévost’s text and its dispositive structure (books, volumes, installments).